Factors Associated with Mothers’ Participation in Bringing Toddlers (Aged 12–36 Months) to the Integrated Health Post (Posyandu) in Helvetia Village, Sunggal Subdistrict, Deli Serdang Regency - Samosir, Yohana; Simamora, Debora Lestari (COVID-19 : Journal of Health, Medical Records and Pharmacy, 2025)
The morbidity and mortality rates of mothers and children remain critical public health concerns in Indonesia. Posyandu (Integrated Health Service Post), as a Community-Based Health Effort (UKBM), plays a vital role in child health maintenance, especially through mothers' active participation in bringing their toddlers for health services. This study aims to identify the factors associated with mothers’ activeness in bringing toddlers (aged 12–36 months) to Posyandu in Helvetia Village, Sunggal Subdistrict, Deli Serdang Regency, in 2023. An analytical survey with a cross-sectional approach was employed, involving 72 mothers selected through purposive sampling. Data were collected using questionnaires and analyzed using the chi-square test. The results showed that the majority of mothers (66.7%) were inactive in taking their toddlers to Posyandu. There was a significant relationship between mothers’ activeness and knowledge (p=0.001), employment status (p=0.000), husband’s support (p=0.000), and attitude (p=0.000). Mothers with good knowledge, who were unemployed, received support from their husbands, and had a positive attitude were more likely to actively attend Posyandu. These findings highlight the importance of educational interventions and social support in increasing mothers’ participation in Posyandu, which is essential for optimizing child growth and development.